Relative bioavailability of selenium yeast, selenomethionine, hydroxyl-selenomethionine and nano-selenium for broilers - Liu, Guoqing; Cao, Sumei; Huang, Liang; Lin, Xuanxu; Sun, Zheng; Lin, Gang; Zhang, Liyang; Lu, Lin; Luo, Xugang; Liao, Xiudong (Frontiers in Veterinary Science, 2025)
Selenium (Se) is an essential trace element for humans and animals. Development and application of new forms of Se sources with lower toxicity and higher bioavailability has been attracting more attention. However, the bioavailabilities of Se from several new Se sources for broilers remain unclear. Therefore, the aim of this study was to assess the relative bioavailabilities of Se from Se yeast (SY), selenomethionine (SM), hydroxyl-selenomethionine (SO) and nano-Se (NS) relative to sodium selenite (SS) for broilers fed a conventional corn-soybean meal diet. A total of 576 one-day-old Arbor Acres commercial male broilers were randomly assigned to 16 treatments with 6 replicate cages per treatment in a completely randomized design involving a 5 (Se sources: SY, SM, SO, NS and SS) × 3 (added Se levels: 0.15, 0.30 and 0.45 mg Se/kg) factorial design of treatments plus 1 (a Se-unsupplemented control) for 21 d. The relative bioavailabilities of Se sources were estimated based on plasma or tissue Se concentrations as well as selenoprotein mRNA expressions and activities in broilers. The results showed that the Se concentrations and glutathione peroxidase (GPX) activities in plasma, liver, breast muscle, pancreas and kidney as well as Se concentration in erythrocytes of broilers, and Gpx1 and Selenop mRNA expressions in pancreas increased linearly (p < 0.03) as added Se level increased. Furthermore, the differences (p < 0.05) among different Se sources were detected for the Se concentrations in liver, breast muscle, pancreas and erythrocytes, GPX activities in pancreas and kidney. Based on slope ratios from the multiple linear regressions of the above indices, the Se bioavailabilities of SY, SM, SO, NS relative to SS (100%) were 78 to 367%, 67.8 to 471%, 57 to 372%, and 45 to 92%, respectively. The results from this study indicated that the Se from SM, SY and SO are more available to broilers than the Se from SS in enhancing the Se concentrations in liver, breast muscle, pancreas and erythrocytes and GPX activity in pancreas, and the Se from SM had the highest while the Se from NS had the lowest relative bioavailability.